Peningkatan Hasil Belajar Peserta Didik Dengan Metode Cooperatif Learning Tipe Tgt Pada Mata Pelajaran Biologi Kelas X.7 Di SMAN 1 Pekanbaru - Wan Roswita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
An Action Research was done in class x.7 of SMAN 1 Pekanbaru becausestudents’ achievement tends to be decreased that is caused by the minimal participation ofthe students in learning process even though it is in discussion classes. The research subjectis class x.7 that consists of 13 male student and 16 females. The method of CooperationLearning Type TGT is one of the suitable methods to make students involved more activeand creative in learning process. In Research was done in two cyeles of 8 meetings, the firstand the fifth meeting were the experimental class. At the end of meetings there was atournament to gather group ccore. Every cycles was ended by daily test and observationsheet. The Result of the research shows that there is increasing of students’ participation inlearning process during the class observation. There is also a significant increasing ofstudents’ achievement from cycle 1 to cycle 2 that the increasing of the average score of55,35 to 70,17 in cycle 1 and 72,62 in cycle 2. The number of students who passed KKM(minimal score) is also increased from 6 students (20,69%) to 18 students (62,07%) and 23students (79,31%). However, the classical students’ achievement couldn’t pass 85% yetwhether in cycle 1 or in cycle 2.